2010
DOI: 10.1158/0008-5472.can-09-3028
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Histone Deacetylase in Cancer Cells Slows Down Replication Forks, Activates Dormant Origins, and Induces DNA Damage

Abstract: Protein acetylation is a reversible process regulated by histone deacetylases (HDAC) that is often altered in human cancers. Suberoylanilide hydroxamic acid (SAHA) is the first HDAC inhibitor to be approved for clinical use as an anticancer agent. Given that histone acetylation is a key determinant of chromatin structure, we investigated how SAHA may affect DNA replication and integrity to gain deeper insights into the basis for its anticancer activity. Nuclear replication factories were visualized with confoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
109
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(121 citation statements)
references
References 49 publications
9
109
1
2
Order By: Relevance
“…However, the later downregulation of BER enzymes is still significant as it likely contributes to the continued or accelerated accumulation of DNA damage. Moreover, while we observed overlap in the DNA repair genes downregulated by LAFPs and vorinostat, the literature suggests that there are possibly other repair genes and pathways uniquely regulated by either as well (12,14,15,28). Indeed, we found that several DSB repair genes were down regulated by HDI, LAFP, or both ( Supplementary Fig.…”
Section: Waf1mentioning
confidence: 56%
See 2 more Smart Citations
“…However, the later downregulation of BER enzymes is still significant as it likely contributes to the continued or accelerated accumulation of DNA damage. Moreover, while we observed overlap in the DNA repair genes downregulated by LAFPs and vorinostat, the literature suggests that there are possibly other repair genes and pathways uniquely regulated by either as well (12,14,15,28). Indeed, we found that several DSB repair genes were down regulated by HDI, LAFP, or both ( Supplementary Fig.…”
Section: Waf1mentioning
confidence: 56%
“…by numerous mechanisms (11)(12)(13)(14)(15). In this work, we examined whether expression of LAFPs would improve response to HDI treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7A and B). Notably, it has recently been demonstrated that HDAC inhibition slows replication and leads to replication-associated DNA damage and H2AX phosphorylation, 50 and we suspect that this is likely to be the cause of the TSA-induced peri-heterochromatic gH2AX seen here. Thus increased background H2AX phosphorylation and the redistribution of topoisomerase IIβ are likely to be independent effects of the TSA-mediated remodelling of heterochromatin.…”
Section: A Fraction Of Topoisomerase Iiβ Is Concentrated In Heterochrmentioning
confidence: 60%
“…In this study, NaB inhibited primary colony-forming potential and regeneration of SP cells, indicating suppression of self-renewal capacity. Most recently, Conti and colleagues showed that SAHA treatment of cancer cells slows down replication forks, activates dormant origins, and induces DNA damage (40). They also found gH2AX could be used as a convenient pharmacodynamic biomarker for HDACi-induced DNA damage (41).…”
Section: Discussionmentioning
confidence: 99%